Agriculture 'East of the Elbe' and the Common Agricultural Policy. Issue 3 (10th July 2013) - Swain, Nigel
Abstract This article explores some of the ambiguities inherent in applying a model of Western European agriculture (the model implicit within the tried and tested modalities of the Common Agricultural Policy (CAP)) to the very different agrarian structures of Central and Eastern Europe. It identifies first the dramatic and long‐standing differences in agrarian structures between these two European regions before considering some of the policy consequences of applying an agricultural support model based on the former to the latter as the CAP (albeit in a slightly modified form initially) was extended to the Accession States. The effect was to exacerbate what many see as perverse features of the CAP. A greater degree of reflexivity on the part of policymakers might have avoided some of these anomalies, but the research agenda of the last half century has left much relating to the CAP unexplored, including agriculture 'east of the Elbe'.